FIELD TRIP: PEMBENTUK HABITUASI LITERASI DIGITAL MAHASISWA SEJARAH PERADABAN ISLAM UIN SALATIGA TAHUN 2023 - Setyaningsih, Wahyu (Universitas Negeri Malang, 2025)
The digital ecosystem is a state that cannot be separated from today's life, including the world of education. History students must have digital literacy skills and habits. Field trips are one of the methods of learning history in getting used to digital literacy. So, the purpose of this study is to describe the field trip of students of the history of Islamic civilization; and analyze field trips in shaping digital literacy habituation of Islamic Civilization History students of UIN Salatiga. The method in this study is field research with a critical historical approach. Data collection techniques through interviews, observations, documentation, and triangulation. The results of this study show that field trips are carried out in temples of the Ancient Mataram Kingdom, Magelang, and Yogyakarta areas. Digital literacy habituation is carried out by assigning information searches through students' smartphones. The results of these activities were then cross-checked in the field with interviews with guides and field observations. Digital literacy habituation is also formed by the activity of taking photos of the objects visited. The data from documentation, interviews, and observations of the temples were then analyzed using a critical historical approach (heuristic, criticism, interpretation, and historiography). Students then make a short article that is uploaded on Instagram. So the results of digital literacy habituation from field trip activities in the form of digital skills, digital ethics, digital security, and digital culture are owned by students.